Coulson & Richardson's chemical engineering. Vol. 3, - Richardson, J. F.; Peacock, D. G. 1927-; Coulson, J. M. (Pergamon, 1994)
The publication of the third edition of 'Chemical Engineering Volume 3' marks the completion of the re-orientation of the basic material contained in the first three volumes of the series. Volume 3 is devoted to reaction engineering (both chemical and biochemical), together with measurement and process control. This text is designed for students, graduate and postgraduate, of chemical engineering.
Keywords: Chemical engineering.; elektronické knihy; electronic books